Evaluation of risk factors, endoscopic characteristics, and severity in patients with acute esophageal variceal bleeding - Vĩnh, Khánh; Le, Van Huy; Pham, Ni Nong; Nguyen, Dang Ngoc; Nguyen, Thi Thuy Linh; Hoang, Thanh Cong (Tạp chí Y Dược Huế, 2026)
Background: Upper gastrointestinal bleeding (UGIB) is a medical and surgical emergency with a poor prognosis. Upper gastrointestinal endoscopy remains the gold standard for diagnosing esophageal variceal. However, the integration of risk factors, clinical and endoscopic findings plays a crucial role in formulating treatment strategies, prognostication, and preventing rebleeding in patients with Upper gastrointestinal bleeding. Subjects and methods: A cross-sectional study conducted on 38 patients with Acute esophageal variceal Bleeding at the Gastrointestinal Endoscopy Center, Hue University of Medicine and Pharmacy Hospital from November 2023 to November 2024. Results: Melena was the most common symptom in patients with Acute esophageal variceal bleeding. Grade III esophageal variceal were the most common endoscopic finding, present in 65.9% of patients. Other endoscopic findings included: cherry red spots: 57.8%; red wale marks: 26.3%; diffuse redness: 8.1%; blood blisters: 7.8%. Lower platelet counts were associated with more severe gastrointestinal bleeding. Grade III esophageal variceal and red wale marks were the most common findings across all severity of gastrointestinal bleeding. Conclusion: Acute esophageal variceal bleeding is a life-threatening complication with high mortality. Risk factors such as medical history, hemoglobin levels, platelet counts, and endoscopic characteristics are related to the extent of bleeding for these patients.